The use Of different varieties of Malaysian English among female teenage Malaysians / Murugan Raj A/L Tanaraj - Murugan Raj, Tanaraj (2014)
This study was to determine the varieties of English used with different people in different domains among female teenage Malaysians. It was also carried out to find out to what extent these respondents are able to switch from the acrolecat to the mesolectal variety of English and at the same time how is language use is related to one’s language identity. The investigation was done by using various instruments such as interviews, reflective journals and questionnaires and written test to obtain much needed information to help facilitate this paper. The main findings were that these respondents use the mesolectal variety when they are communicating with their peers who are less proficient in English and family members and at the same time they use the acrolectal variety when they are in formal domains such as during examinations and English lessons in schools. These respondents were also able to switch from one variety to another according to their needs. It also revealed that the respondents were able to take up different roles at different domains. It was concluded that teenagers are able to use the varieties of English mentioned earlier, according to the domains and the people they are with and at the same time switch from one variety to another accordingly. It can also be concluded that the respondents take up different identities to avoid ‘othering’ and they resort to ‘styling’ to blend into the group that they are in and this means that language plays a pertinent role in forming identities